O Rural e o Virtual: a cultura local do distrito rural de Guaragi, Ponta Grossa - PR e o uso da Internet - Coneglian, Flavio Marcelo (2015)
This study aims to understand how the local rural culture of Guaragi district, Ponta Grossa - PR is reworks using the Internet. Thus, the discussions revolve around the dialectical relationship between modes of rural and urban life. The field data collection relies on the application of two quantitative questionnaires, one for residents who have Internet access and one for residents who have no contact with it in their daily lives. The methodology used for the interviews is the saturation data that seeks to acquire information until they do not bring additional contributions to the analysis. The writing of this search consists of three chapters, the first covers theoretical discussions of countryside, city, rural, urban, territoriality and social representations. The second provides content for the globalization process, media, technologies and the creation and expansion of the Internet. The third chapter presents information and analysis with the field research data.